Carnivorous Suspension Feeding by the Subarctic Calanoid Copepod Neocalanus cristatus - Greene, Charles H.; Landry, Michael R. (Canadian Journal of Fisheries and Aquatic Sciences, 1988)
Carnivorous suspension feeding is described for the large subarctic calanoid copepod Neocalanus cristatus. This foraging mode relies on the use of a feeding current to entrain potential prey items and transport them into the copepod's capture area. The extensive use of a feeding current to entrain and transport prey into the capture area distinguishes carnivorous suspension feeding from the predatory modes typically described for other calanoid copepods. The consequences of carnivorous suspension feeding on N. cristatus' prey-selection patterns are significant. Feeding experiments reveal that the vulnerability of naupliar prey declines with increasing prey size, just the opposite result observed for other marine calanoids exhibiting more typical predatory feeding modes. The role of omnivorous feeding by N. cristatus within the pelagic ecosystem of the subarctic Pacific is also discussed. In contrast with earlier hypotheses, the results reported here are consistent with the emerging view that this large suspension-feeding copepod may be having at least as great an impact on the microzooplankton as on the phytoplankton of the region.